Efficacy of Pericardium 6 Acupressure in Reducing Nausea and Vomiting in First Trimester Pregnant Women - Usman, Hastuti; Muliani, Muliani; Feby, Feby; Nurfatimah, Nurfatimah; Silfia, Niluh Nita (Universitas Andalas, 2024)
This study investigates the effect of acupressure on the pericardium 6 (PC6) point in reducing nausea and vomiting among pregnant women during the first trimester. Utilizing a pre-experimental design with a one-group pretest-posttest approach, the research was conducted with 85 pregnant women from the Mamboro Health Center area. A consecutive sampling technique was used to select a sample of 15 respondents. The study employed the Pregnancy-Unique Quantification of Emesis Nausea (PUQE-24) questionnaire to measure nausea and vomiting severity. Results showed that prior to acupressure treatment, 80% of participants experienced moderate nausea and vomiting, while 20% had mild symptoms. Following the application of PC6 acupressure, 80% of participants reported mild symptoms, and only a moderate category remained. The Wilcoxon test yielded a p-value of 0.003, indicating a statistically significant reduction in symptoms (p < 0.05). The findings suggest that acupressure on the pericardium 6 point effectively reduces nausea and vomiting in pregnant women during their first trimester in the Mamboro Health Center area.